Detección de niveles de proteinuria y su relación con la presencia de cilindros en sedimento urinario, como biomarcadores de daño renal, en pacientes diabéticos e hipertensos hospitalizados en el área de clínica del Hospital Provincial Isidro Ayora de la ciudad de Loja - Mina Corozo, María Paola (2015)
In the actuality renal disease in diabetic and hypertensive patients are very frequent, causing chronic kidney damage or chronic global renal disease, with a high mortality rate so for detection 24-hour urine and partial urine is used, which are processed using appropriate techniques and methods for their determination. This study was used to detect levels of proteinuria and its relation to the presence of cylinders in urinary sediment, as biomarkers of renal injury in diabetic hypertensive patients and hospitalized in the clinic area Isidro Ayora provincial hospital in the city of Loja; and for the detection of proteinuria 24 hours, using the techniques and procedures, also held detection cylinder urinalysis in the first morning urine of the study population, and a comparative analysis of results, was also result obtained, diabetic and hypertensive patients; for conducting this research we worked with a sample of 59 patients of which 31 were diabetic and 28 hypertensive patients, using corresponding methods and, techniques for the detection of 24-hour, proteinuria was processed by quantitative technique performed by the method turbidimetric Cobas-C311 in the computer, was used Roche reagent (Gen TPUC, 3, 150t, Cobas C311) for detecting urinary sediment, cylinder technique for direct observation of the same was employed. 26% in diabetic patients increased proteinuria, cylinders presence of 45% was obtained; 21% in hypertensive patients increased proteinuria and cylinders presence of 36% was obtained. Upon completion of this study, it was found that diabetic patients are those most at risk to suffer kidney damage unlike patients with hypertension; it is important that patients regularly come to the Hospital Isidro Ayora to monitor your blood pressure, proteinuria 24 hours, elementary and microscopic urine to avoid further complications. Keywords: Proteinuria, Cylinders, Diabetic, Hypertensive.